2003
DOI: 10.1071/ea02081
|View full text |Cite
|
Sign up to set email alerts
|

Performance of some perennial grasses on severely salinised sites on the inland slopes of New South Wales

Abstract: Thirty perennial grass accessions were evaluated for emergence, growth and persistence at 6 severely salinised seepage scalds on the western slopes of New South Wales. Warm-season accessions were sown or planted in spring 1996 and 1997, and cool-season types in autumn 1996 and 1997. Control species, tall wheat grass (Thinopyrum ponticum) and puccinellia (Puccinellia ciliata) were sown in spring and autumn. Plants were monitored over 2 growing seasons. None of the accessions, including the controls, performed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 6 publications
5
15
1
Order By: Relevance
“…Seashore paspalum ( Paspalum vaginatum Swartz), a halophytic warm season grass, has recently gained interest for use on saline turfgrass and forage sites, drainage water reuse schemes, and land reclamation under saline conditions (Duncan and Carrow, 2000; Semple et al, 2003; Grattan et al, 2004; Rogers et al, 2005). Seashore paspalum exhibits a wide range in salinity tolerance among ecotypes (Lee et al, 2004b, 2005).…”
mentioning
confidence: 99%
“…Seashore paspalum ( Paspalum vaginatum Swartz), a halophytic warm season grass, has recently gained interest for use on saline turfgrass and forage sites, drainage water reuse schemes, and land reclamation under saline conditions (Duncan and Carrow, 2000; Semple et al, 2003; Grattan et al, 2004; Rogers et al, 2005). Seashore paspalum exhibits a wide range in salinity tolerance among ecotypes (Lee et al, 2004b, 2005).…”
mentioning
confidence: 99%
“…Paspalum vaginatum is one of the species of the genus with highest salt tolerance (Uddin, Juraimi, Ismail, Othman, & Rahim, ). There are records about its introduction for forage and turf use under saline conditions and its ability for rehabilitation of saline soils (Duncan & Carrow, ; Grattan et al., ; Rogers et al., ; Semple, Cole, & Koen, ). Marcum and Murdoch () and Lee, Carrow, Duncan, Eiteman, and Rieger () found that accumulation of organic solutes and the uptake of inorganic ions are the main mechanisms responsible for osmotic adjustment and tolerance to salt stress in this species.…”
Section: Agronomic Characterization and Selection Criteriamentioning
confidence: 99%
“…The soil salinity levels recorded where the puccinellia and samphire were present in this study were higher than expected. Samphire has been reported to show its best growth at soil salinity levels of 25 -40 dS/m ( Barrett-Lennard et al 2013) and puccinellia has previously been reported to show its best growth at soil salinity levels of 16 -32 dS/m (Semple et al 2003) and 13 -24 dS/m in the top 30 cm (Hamilton 1972). It can also withstand periodic flooding under these conditions (Rogers and Bailey 1963).…”
Section: Insert Figure 4 Herementioning
confidence: 99%